Particulate air pollution (pm2.5 and pm10 ) and medical consultations due to respiratory disease in Medellín (2008-2009) - Carlos F. Gaviria G; Paula C. Benavides C; Carolina A. Tangarife (Universidad de Antioquia, 2011)
Scientific evidence shows how air pollution has negative effects on human health. Medellin city (Colombia) has high levels of air pollution (according to Redaire's measurements) as well as a high rate of medical and emergency consultations due to respiratory disease (according to Metrosalud's measurements). Objective: to show statistical evidence of the positive relationship between pollution due to pm2.5 and pm 10 particulate matter and the medical and emergency consultations due to respiratory diseases (asthma, bronchitis, infections, and rhinitis). Methodology: a number of time series models were applied on daily records of pm 10 and pm 2.5 particles. A total of ten models were calculated using ordinary least squares (OLS) with White's correction in order to adjust heteroskedasticity problems. Initially, five models were used for the consultations caused by respiratory disease and pm10 particles. Then, five additional models were used for the consultations caused by respiratory diseases and pm 2.5particles. Results: particulate air pollution leads to respiratory disease, thus becoming a public health problem in Medellín, Colombia.